Falls and Prevention of Fall Outcomes. (11th November 2018) - Duthie, E; Simpson, D; Myers, J; Denson, K; Denson, S
Abstract: Falls are an important geriatric syndrome with serious outcomes. Use of benzodiazepines, non-benzodiazepine hypnotics, and diphenhydramine increases the risk for falls and is modifiable. An interprofessional team created a falls and medication related Maintenance of Certification (MOC) Part IV activity for primary care physicians (PCPs) to meet American Board of Medical Specialists requirements. The activity prepares PCPs to initiate brief (2–3 min) conversations to reduce medication use by discussing its relationship to falls with geriatric patients. The MOC was launched as a workshop at a statewide PCP meeting using interactive educational strategies (quiz, patient educational tools, role play). A retrospective "post-post" evaluation assessed workshop processes and outcomes. 100% of attendees (14/14) completed the workshop evaluation. Analysis found very positive responses: 1) perceived decrease for 4 literature-based barriers to medication discussions; 2) increased likelihood to initiate conversations with patients about medications and falls; and 3) all were likely to recommend the session to a colleague. Participants targeted improvement aims between a 20%-50% increase in medication use conversations in their practices. Participants emphasized workshop's foci on developing and testing scripts for conversations and utilization of proven patient education materials were key elements in likelihood to have conversations. PCPs initially perceived medication and falls discussions as fraught with barriers. A brief (90 min) interactive MOC activity reduced perceived barriers and increased PCP commitment to conduct medication and falls discussions with geriatric patients.